ANALISIS SISTEM PENGAMAN BACKUP UNTUK MENGAMANKAN BUSBAR 150 Kv TERHADAP GANGGUAN DI GIS PECATU - Wardana, I Nyoman; Dyana Arjana, I Gede; Indra Partha, Cok. Gede (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i04.p5, 2022)
High power needs in badung area, especially Pecatu and Nusa Dua resulted in the need for GIS development to increase power supply. GIS Pecatu uses a double busbar with OCR as its Backup safety, if one of the busbars is disrupted and there is no protection rele that secures the busbar, it will result in continuous power flow is disrupted. In this study, an analysis of the rele busbar setting and the appropriate protection setting as a reference protection system in GIS Pecatu. The results of the calculation of current setting obtained the working current value (Iset) OCR of 1339 A and (Iset) GFR 223 A and delay time 0.53 seconds, actual working time rele 0.35 Standard Inverse, and the value of short circuit interference current calculation from PLN 11.58 kA and based on simulation results obtained 11.46 kA with a percentage of errors of 0.12%.